Bevacizumab-loaded CalliSpheres beads: in vitro loading, release profiles and application in rabbit liver VX2 tumor model - Ren, Kewei; Li, Yahua; Zhou, Zihe; Wu, Kunpeng; Wang, Jianan; Yao, Jianning; Li, Yifan; Ge, Xiaoyong; Li, Xiao; Li, Zhen; Li, Zongming; Han, Xinwei (Frontiers in Oncology, 2023)
Background Bevacizumab loaded drug-eluting beads have the potential to reduce TACE related VEGF expression. The purpose of this study was to investigate the in vitro loading, and release profiles of bevacizumab (BEV) loaded on Callispheres beads (CB) and its application in rabbit liver VX2 tumor model. Methods CB with sizes of 100-300 um and 300-500 um were divided into 5 groups, respectively. BEV with different content was prepared for CB loading, releasing and detected in the solution at different time points. The diameters of CB in each group were measured under a light microscope to calculate the shrinkage rate. The rabbit with VX2 liver model were divided into control group, CB-TACE group, CB-TACE+BEV group, and BEV group. The data of blood test, CT image, HE and IHC staining were compared and analyzed. Results The shrinkage rate of the 100-300 um CB was 2.6-7.2%, while the 300-500 um CB was 0.2-7.1%. The BEV-loaded CB (BEV-CB) has a burst release during the first hour and following gradually released with time. The release profiles of 100-300 um CB reach 34% in 24 hours, while the 300-500 um CB to 25.8%. BEV-CB with sizes of 100-300 um was chosen to perform transcatheter arterial chemoembolization (TACE). The results showed that BEV-CB-TACE not only gradually increased the content of BEV in serum and organ tissue but also reduced the level of VEGF in serum. Pathological results suggested that the expression of HIF-1 was elevated while VEGF and MVD decreased when compared to the other groups. Conclusion In conclusion, this study confirms that Callispheres beads could efficiency loaded BEV. BEV-CB-TACE has a good safety and effectiveness, and its application could reduce the level of VEGF-A in serum in the treatment of VX2 tumors.